Room-temperature high-speed electrical modulation of excitonic distribution in a monolayer semiconductor - Guangpeng Zhu; Lan Zhang; Wenfei Li; Xiuqi Shi; Zhen Zou; Qianqian Guo; Xiang Li; Weigao Xu; Jiansheng Jie; Tao Wang; Wei Du; Qihua Xiong (Nature Communications, 2023)
Abstract Excitons in monolayer semiconductors, benefitting from their large binding energies, hold great potential towards excitonic circuits bridging nano-electronics and photonics. However, achieving room-temperature ultrafast on-chip electrical modulation of excitonic distribution and flow in monolayer semiconductors is nontrivial. Here, utilizing lateral bias, we report high-speed electrical modulation of the excitonic distribution in a monolayer semiconductor junction at room temperature. The alternating charge trapping/detrapping at the two monolayer/electrode interfaces induces a non-uniform carrier distribution, leading to controlled in-plane spatial variations of excitonic populations, and mimicking a bias-driven excitonic flow. This modulation increases with the bias amplitude and eventually saturates, relating to the energetic distribution of trap density of states. The switching time of the modulation is down to 5 ns, enabling high-speed excitonic devices. Our findings reveal the trap-assisted exciton engineering in monolayer semiconductors and offer great opportunities for future two-dimensional excitonic devices and circuits.